A penetração do neoliberalismo na saúde pública brasileira: o caso da cidade de Itu/SP - Macruz, Rodrigo Oliveira (2024)
The research in question addresses the outsourcing of public health services through OSS (Social Health Organizations). This process was only made possible by the Administrative Reform in Brazil during the period from 1995 to 1998, under the first term of President Fernando Henrique Cardoso, through Constitutional Amendment 19/1998. This amendment enabled the regulation of public health outsourcing in Brazil, thereby initiating the process of integrating neoliberalism into Brazilian healthcare. The reform was developed and implemented by the Ministry of Federal Administration and State Reform (MARE), under the leadership of Minister Luiz Carlos Bresser Pereira. It was systematically organized in its concepts, guidelines, objectives, and strategies through the Master Plan for State Apparatus Reform. The reform followed the model of the British reform led by then-Prime Minister Margaret Thatcher, through the framework of New Public Management, which dismantled the welfare state. According to the reform, the state must reduce expenditures and, to this end, outsource the implementation of public policies. The public sector would no longer be able to carry out such functions as it previously did. Consequently, the state was to adopt an austere and efficient stance, establishing partnerships with organized civil society through OSS (Social Health Organizations) and OSCIPs (Civil Society Organizations of Public Interest). With this shift, the state's role became predominantly regulatory, while execution activities were delegated to third parties, following the directives of the neoliberal model. The State Reform prepared the country for neoliberalism, adhering to all the guidelines of the Washington Consensus, and opened the Brazilian market to globalized companies, leading to significant transformations in the national economy. The analysis focuses on the State Reform, the MROSC (Regulatory Framework for Civil Society Organizations), the SUS (Unified Health System), and all aspects of public health outsourcing through OSS. The study specifically examines the privatization of Brazilian public health via OSS, using the city of Itu as a case study, where public health services were outsourced to the OSS named *Camino de Damasco*. The research aims to elucidate whether neoliberalism has indeed been integrated into public health within the municipality